Telehealth utilization during the Covid-19 pandemic: A systematic review. (November 2021) - Garfan, Salem; Alamoodi, A.H.; Zaidan, B.B.; Al-Zobbi, Mohammed; Hamid, Rula A.; Alwan, Jwan K.; Ahmaro, Ibraheem Y.Y.; Khalid, Eman Thabet; Jumaah, F.M.; Albahri, O.S.; Zaidan, A.A.; Albahri, A.S.; et al.
Abstract: During the coronavirus disease (COVID-19) pandemic, different technologies, including telehealth, are maximised to mitigate the risks and consequences of the disease. Telehealth has been widely utilised because of its usability and safety in providing healthcare services during the COVID-19 pandemic. However, a systematic literature review which provides extensive evidence on the impact of COVID-19 through telehealth and which covers multiple directions in a large-scale research remains lacking. This study aims to review telehealth literature comprehensively since the pandemic started. It also aims to map the research landscape into a coherent taxonomy and characterise this emerging field in terms of motivations, open challenges and recommendations. Articles related to telehealth during the COVID-19 pandemic were systematically searched in the WOS, IEEE, Science Direct, Springer and Scopus databases. The final set included (n = 86) articles discussing telehealth applications with respect to (i) control (n = 25), (ii) technology (n = 14) and (iii) medical procedure (n = 47). Since the beginning of the pandemic, telehealth has been presented in diverse cases. However, it still warrants further attention. Regardless of category, the articles focused on the challenges which hinder the maximisation of telehealth in such times and how to address them. With the rapid increase in the utilization of telehealth in different specialised hospitals and clinics, a potential framework which reflects the authors' implications of the future application and opportunities of telehealth has been established. This article improves our understanding and reveals the full potential of telehealth during these difficult times and beyond. Highlights: State-of-the-art Literature Categorization for Telehealth utilization during COVID-19. Challenges, motivations and recommended solutions are identified for Telehealth during COVID-19. Different Applications of Telehealth during the COVID-19 pandemic.